2018
DOI: 10.1074/jbc.ra118.003037
|View full text |Cite
|
Sign up to set email alerts
|

C-terminally truncated, kidney-specific variants of the WNK4 kinase lack several sites that regulate its activity

Abstract: WNK lysine-deficient protein kinase 4 (WNK4) is an important regulator of renal salt handling. Mutations in its gene cause pseudohypoaldosteronism type II, mainly arising from overactivation of the renal Na/Cl cotransporter (NCC). In addition to full-length WNK4, we have observed faster migrating bands (between 95 and 130 kDa) in Western blots of kidney lysates. Therefore, we hypothesized that these could correspond to uncharacterized WNK4 variants. Here, using several WNK4 antibodies and WNK4 mice as controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…2, C, D, G, and H), indicating that ZnD stimulates phosphorylation of all expressed NCC. In support of this, a recent study implicated a Zn 2ϩdependent metalloprotease in regulation of WNK kinases, critical NCC regulators (16). Calcineurin is also a Zn 2ϩregulated phosphatase (17,23) linked to NCC phosphorylation (10).…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…2, C, D, G, and H), indicating that ZnD stimulates phosphorylation of all expressed NCC. In support of this, a recent study implicated a Zn 2ϩdependent metalloprotease in regulation of WNK kinases, critical NCC regulators (16). Calcineurin is also a Zn 2ϩregulated phosphatase (17,23) linked to NCC phosphorylation (10).…”
Section: Discussionmentioning
confidence: 90%
“…Zn 2ϩ is an essential cofactor that influences the expression and activity of numerous enzymes, transcription factors, and regulatory proteins. Recently, it was suggested that a Zn 2ϩ -dependent metalloprotease may regulate with-no-lysine kinase (WNK) kinases, powerful regulators of NCC (16). However, a direct link between NCC and ZnD-induced BP dysregulation has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the opposite effects of CaSR activation on NKCC2 vs. NCC deserve further clarification. Several C-terminally-truncated WNK4 variants have been identified in the kidney, including variants with increased, as well as decreased catalytic activity towards SPAK [94]. The described C-terminal truncations may eliminate the putative CaM-binding site (amino acids 1175-1194), thereby abrogating the inhibitory effects of [Ca 2+ ] i on WNK4 activity [69,94].…”
Section: Casr Function In Dctmentioning
confidence: 99%
“…Several C-terminally-truncated WNK4 variants have been identified in the kidney, including variants with increased, as well as decreased catalytic activity towards SPAK [94]. The described C-terminal truncations may eliminate the putative CaM-binding site (amino acids 1175-1194), thereby abrogating the inhibitory effects of [Ca 2+ ] i on WNK4 activity [69,94]. Assuming distinct distribution of WNK4-variants between TAL and DCT, it is tempting to speculate that the truncated WNK4 variants lacking the inhibitory CaM-binding site but preserving the SPAK-binding motif are enriched in DCT.…”
Section: Casr Function In Dctmentioning
confidence: 99%
See 1 more Smart Citation